Application of Appropriate Technology for Screening, Diagnosis and Evaluation of Congenital Heart Disease in Neonates in Hainan Province - ZHANG Dufei, CHEN Renwei, MO Zelai, YANG Ling, WANG Yazhou, WANG Haifan (Zhongguo quanke yixue, 2023)
Background Congenital heart disease (CHD) is one of the major types of birth defects in the world, which is the leading cause of death in children. However, the current situation of delayed diagnosis of CHD is not optimistic, making the early detection, diagnosis and treatment of children with CHD a hot research topic. Objective To establish and apply the appropriate technology system for screening, diagnosis and evaluation of CHD in neonates in Hainan Province, evaluate operational effect of the technology for its further promotion. Methods In accordance with the requirements of the Program of Neonatal CHD Screening Project issued by the National Health Commission, the relevant literatures were reviewed to establish the appropriate technology system for screening, diagnosis and evaluation of CHD in neonates, in which screening staff perform CHD screening on liveborn neonates within 6-72 hours after birth using integration of cardiac murmur auscultation and transcutaneous pulse oximetry (POX) , in all midwifery institutions of 17 cities and counties in Hainan province, as well as the local neonatology departments or neonatal intensive care units (NICUs) . Positive results of heart murmur auscultation and/or POX were considered positive for screening. 31 diagnostic facilities authorized by Hainan Provincial Health Commission were responsible for the echocardiography examinations for liveborn neonates with positive screening results. The qualified cardiovascular physicians and cardiac surgeons in the 6 certified tertiary hospitals reviewed the diagnosis results and made necessary re-evaluations, suggested or implemented medical intervention and proposed suggestions on clinical follow-up (3 to 12 months) according to the conditions. Screening, diagnosis, evaluation and treatment data were filled, uploaded and managed online through the neonatal CHD screening information management network. The operational effectiveness of this appropriate health technology was evaluated in 17 cities (counties) in Hainan Province from 2020-01-01 to 2021-12-31. Results From 2020-01-01 to 2021-12-31, the count of liveborn neonates in Hainan Province was 206 761, 204 442 of them were included in the screening program with an overall screening rate of 98.88% and screen-positive rate of 2.86% (5 847/204 442) . A total of 527 cases diagnosed with CHD by echocardiography, showing a CHD prevalence of 2.58‰ (527/204 442) , and atrial septal defect as the most common CHD lesion with a composition ratio of 38.14% (201/527) , including 291 insignificant type CHD cases (55.22%) , 142 significant type CHD cases (26.94%) , 88 serious type CHD cases (16.70%) and 6 critical type CHD cases (1.14%) . The sensitivity of auscultation, POX and combination of 2 indicators for CHD screening was 67.93%, 37.00% and 93.35%, respectively, and the specificity was 98.07%, 99.28% and 97.30%, respectively. Neonates with positive results for both indicators (heart murmur auscultation and POX) were more likely to suffer from severe CHD (severe and critical types) than those with positive results for a single indicator (P<0.001) . A total of 94 cases with severe CHD were treated promptly. A total of 4 cases with severe CHD died, the standardized mortality of neonates aged 0-1 year with CHD was 1.96/100 000, the mortality rate of neonates with severe CHD was 4.26% (4/94) . Conclusion The combination of two indicators (heart murmur auscultation and POX) for CHD screening is favorable to promotion for the characteristics of noninvasion, simplicity, ease of operation and reliability. The establishment of appropriate technology system for screening, diagnosis, and evaluation of neonatal CHD is of great significance for its advantages in the timely diagnosing and treatment of CHD, especially in severe CHD, and reduction of mortality in neonates with CHD.